2006
DOI: 10.1080/15572536.2006.11832616
|View full text |Cite
|
Sign up to set email alerts
|

A molecular phylogeny of the flagellated fungi (Chytridiomycota) and description of a new phylum (Blastocladiomycota)

Abstract: Chytridiomycota (chytrids) is the only phylum of true Fungi that reproduces with motile spores (zoospores). Chytrids currently are classified into five orders based on habitat, zoospore characters and life cycles. In this paper we estimate the phylogeny of the chytrids with DNA sequences from the ribosomal RNA operon (18S+5.8S+28S subunits). To our surprise the morphologically reduced parasites Olpidium and Rozella comprise two entirely new, and separate, lineages on the fungal tree. Olpidium brassicae groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
265
0
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(287 citation statements)
references
References 48 publications
10
265
0
12
Order By: Relevance
“…Intriguingly, there was also an increase in abundance of Massilia OTUs. Massilia is able to degrade chitin (Faramarzi et al, 2009;Adrangi et al, 2010) found in the fungus cell wall (James et al, 2006). It may also explain the repeated observation that Massilia is abundant in the rhizosphere (Bodenhausen et al, 2013) and found to be associated with soils colonised by pathogenic fungi like Fusarium and Rhizoctonia solani (Klein et al, 2013;Yin et al, 2013).…”
Section: Succession Of the Rhizosphere Microbiotamentioning
confidence: 70%
See 1 more Smart Citation
“…Intriguingly, there was also an increase in abundance of Massilia OTUs. Massilia is able to degrade chitin (Faramarzi et al, 2009;Adrangi et al, 2010) found in the fungus cell wall (James et al, 2006). It may also explain the repeated observation that Massilia is abundant in the rhizosphere (Bodenhausen et al, 2013) and found to be associated with soils colonised by pathogenic fungi like Fusarium and Rhizoctonia solani (Klein et al, 2013;Yin et al, 2013).…”
Section: Succession Of the Rhizosphere Microbiotamentioning
confidence: 70%
“…There was also a similar increase in abundance of the bacterial genus Massilia, suggesting it may be related to this invasion. Since this genus grows on chitin as a carbon and nitrogen source (Faramarzi et al, 2009;Adrangi et al, 2010) there may be a causal link, with Massilia growing on material derived from the putative O. brassicae (Figure 4) (James et al, 2006).…”
Section: Microbiota Selection In Compostmentioning
confidence: 99%
“…However, a previous study including five genes in addition to 18S rDNA demonstrates that these organisms are likely not closely related (James et al, 2006b). The 28 OTUs in this unidentified group share only 86.9-93.2% sequence similarity to known cultured isolates representing a variety of phyla (Supplementary Table 1), including those from two newly established phyla, Blastocladiomycota (James et al, 2006a) and Neocallimastigomycota (Hibbett et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Equivalent to euchytrids of James et al 2006, the 'core chytrid clade' of James et al (2007), or the 'core chytrid clade' plus the Monoblepharidales of James et al (2000). Earlier usages are not indicated in the author citation of the name, because the circumscription adopted here differs significantly from that of those authors.…”
Section: Phylogenetic Classification Of Fungimentioning
confidence: 99%
“…The Chytridiomycota is retained in a highly restricted sense, including Chytridiomycetes and Monoblepharidomycetes. The Blastocladiales, a traditional member of the Chytridiomycota, is here treated as a phylum, the Blastocladiomycota, as in James et al (2007). The Neocallimastigales, whose distinctiveness from other chytrids has long been recognized, is also elevated to phylum, based on both morphology and molecular phylogeny.…”
Section: Overview Of the Classificationmentioning
confidence: 99%